2018
DOI: 10.1093/cz/zoy002
|View full text |Cite
|
Sign up to set email alerts
|

Opposed elevational variation in prevalence and intensity of endoparasites and their vectors in a lizard

Abstract: Studying the causes of parasite geographic distribution is relevant to understand ecological and evolutionary processes that affect host populations as well as for species conservation. Temperature is one of the most important environmental variables affecting parasite distribution, as raising temperatures positively affect development, reproduction, and rate of transmission of both endo- and ectoparasites. In this context, it is generally accepted that, in mountains, parasite abundance decreases with elevatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 88 publications
4
23
0
1
Order By: Relevance
“…Prevalence and intensity of hemoparasites was higher in the lowland population. This finding contrasts with other studies reporting an increase in hemoparasite infection with elevation in the eastern genetic lineage of P. algirus (Álvarez-Ruiz et al 2018), but it is consistent with other studies reporting a decrease in hemoparasite infection with elevation in birds (Zamora-Vilchis et al…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Prevalence and intensity of hemoparasites was higher in the lowland population. This finding contrasts with other studies reporting an increase in hemoparasite infection with elevation in the eastern genetic lineage of P. algirus (Álvarez-Ruiz et al 2018), but it is consistent with other studies reporting a decrease in hemoparasite infection with elevation in birds (Zamora-Vilchis et al…”
Section: Discussionsupporting
confidence: 67%
“…In contrast, regarding ectoparasites, we found that prevalence of ticks was higher in the upland population, being anecdotic the presence of ticks in the lowland population, as it has been previously described in the same species and region (Llanos-Garrido et al 2017). However, other studies have reported a decrease in tick abundance with elevation in the eastern genetic lineage of P. algirus (Álvarez-Ruiz et al 2018). Therefore, our findings suggest that patterns of elevational variation of parasitism may be more complex and be also explained by other habitat factors that show elevational variation, rather than just by the altitude per se.…”
Section: R a F Tsupporting
confidence: 58%
“…1994 ; Camacho and Avilés 2019 ). Meanwhile, parasites showed a complex pattern: the prevalence of ectoparasites (mites) decreased linearly with ascending elevation, whereas hemoparasites increased linearly ( Álvarez-Ruiz et al. 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“… Alvarez-Ruiz et al. (2018) characterized an elevational gradient for patterns of ecto- and endoparasitization in the lizard Psammodromus algirus and reported contrasting patterns of decreasing ecto- but increasing endoparasitism with altitude.…”
Section: Contributions To This Issuementioning
confidence: 99%